Abnormal grain growth under solution-aging treatments enables convergence mechanical properties of a Fe-Ni-Cr based austenitic alloy. (1st April 2023) - Li, Jina; Su, Jie; Liu, Geng; Ding, Yali; Wang, Ao; Yu, Linran
Abstract: In this study, systematic heat treatment routes including solution (980 °C to 1130 °C) and aging (675 °C to 775 °C) processes were used to tailor the microstructural evolution and mechanical performance of a Fe-Ni-Cr based austenitic alloy, strengthened by a γ ′ phase (Ni3 (Ti, Al)). Grain growth was observed with increasing solution treatment temperature from nearly 90 μ m (980 °C) to nearly 200 μ m (1130 °C). Grain refinement during solution heat processes was found to ascribe to the solute drag effect and the pinning effect of nickel-titanium-enriched segregates and precipitates. During aging, the precipitation behavior of γ ′ is found to be almost independent of solution treatment temperatures. Interestingly, abnormal grain growth during aging was observed. The motion of grain boundaries was ascribed to the formation of nickel-titanium-enriched γ ′ in the austenitic matrix, thereby contributing to the dissolution of the previously enriched segregates and precipitates from grain boundaries. The studied alloy shows a wide range of mechanical properties, from tensile strength of 1131 MPa with ductility at 36%, to tensile strength of 880 MPa with ductility at 50%. The current study demonstrates that grain refinement of the alloy at solution treatment may not benefit the final mechanical properties.